2013
DOI: 10.1590/s0104-64972013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Prey preference of the stone crab Platyxanthus crenulatus (Decapoda: Platyxanthidae) in laboratory conditions

Abstract: -The preference for a particular type of prey implies an active behavioral choice of the predator. The present work deals with the prey preference of the large stone crab Platyxanthus crenulatus among similar sized gastropods and bivalves of different substrates using a recent proposed methodology based on a two-stage approach. In laboratory, crabs received different mollusk species separately to determine the consumption in number of each species when choice was not possible. Further, crabs were offered the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Nauplius, 25: e2017033 break the shell of prey, attacks effectively and consumes many different sympatric mollusk species, but when faced with a choice it prefers some species over the others (Laitano et al, 2013). Results of the present study also indicated that, although the stone crab E. verrucosa is able to consume all six types of prey offered, the proportion of crab feeding and/or the biomass of prey eaten vary considerably among them: a higher percentage of crab feeding was observed when the mussel M. galloprovincialis, the limpet P. depressa or the sea snail Ph.…”
Section: Predatory Behavior Of the Crab Eriphia Verrucosamentioning
confidence: 99%
See 2 more Smart Citations
“…Nauplius, 25: e2017033 break the shell of prey, attacks effectively and consumes many different sympatric mollusk species, but when faced with a choice it prefers some species over the others (Laitano et al, 2013). Results of the present study also indicated that, although the stone crab E. verrucosa is able to consume all six types of prey offered, the proportion of crab feeding and/or the biomass of prey eaten vary considerably among them: a higher percentage of crab feeding was observed when the mussel M. galloprovincialis, the limpet P. depressa or the sea snail Ph.…”
Section: Predatory Behavior Of the Crab Eriphia Verrucosamentioning
confidence: 99%
“…seems to be a common pattern among large stone crab species (Laitano et al, 2013). The shell rugosity of prey was also relevant since crabs cannot easily attach to a shell with smooth surface (Weigand and Plath, 2013).…”
Section: Predatory Behavior Of the Crab Eriphia Verrucosamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of prey preference studies for E. sinensis, such data are available for other species of decapod crustaceans using a variety of different methods (e.g. Ashton, 2002;Buck et al, 2003;Jackson & Underwood, 2007;Erickson et al, 2008;Grason & Miner, 2012;Haddaway et al, 2012;Laitano et al, 2013). In the present study, methods devised by Taplin (2007) were used, and observations on handling times of the different prey species were also made.…”
Section: Introductionmentioning
confidence: 94%
“…Their claws have marked heterochely and laterality (i.e. dimorphism between chelae and the tendency for them to appear on a particular side of the body), traits associated with shell-breaking feeding habits (Laitano et al 2013). Due to their abundance, large size and diet, P. crenulatus presumably has an important ecological role as a predator in benthic communities, similar to that of other stone crabs such as the Mennipidae in the northwestern Atlantic Ocean (Gerhart and Bert 2008).…”
Section: Introductionmentioning
confidence: 99%